Natural Resource Conservation Behavior of the People Living in the Wat Rai Khing Waterfront Community Nakhon Pathom Province - Changnoi, Anucha (Dhammathas Academic Journal, 2024)
The purposes of this research were; 1) to study the attitudes towards natural resource conservation behavior among the residents of the riverside community near Wat Rai Khing, Nakhon Pathom province, and 2) examine the impact of residents’ behavior on natural resource conservation in the riverside community near Wat Rai Khing, Nakhon Pathom province. It was a quantitative research study. The sample group used in the research consisted of residents living in the riverside community near Wat Rai Khing, Nakhon Pathom province, comprising 14 villages or 28 communities with a total population of 3,200 people. According to Yamane’s formula, a sample group of 356 people was obtained. The research instruments included statistical questionnaires used for data analysis, including frequency, percentage, mean, standard deviation, and Pearson correlation coefficient. The research findings were as follows: 1. The majority of respondents to the questionnaire were males aged between 31-40 years old, married, with education levels ranging from junior high school to vocational certificate, engaged in private businesses, and with an average monthly income of less than 35,000 baht. 2. Destructive behaviors towards natural resources, on average, were significantly high, including unsustainable occupations, the use of hazardous chemicals, and disturbance of aquatic and surrounding life. Overall, natural resource conservation behaviors were significantly high, including fostering understanding of environmental systems, efficient resource utilization, and addressing wastefulness and pollution resulting from human activities. Regarding hypothesis testing of personal factors with destructive behaviors towards natural resources and conservation behaviors, no significant differences were found in any aspect at a statistically significant level of 0.05.